Armed conflict and child labor: evidence from Iraq. Issue 2 (3rd July 2019) - Naufal, George; Malcolm, Michael; Diwakar, Vidya
ABSTRACT: This paper examines the relationship between armed conflict intensity and child labor using household level data from Iraq and taking advantage of a quasi-experimental setup. Armed conflict intensity is measured by the number of deaths related to conflict, and child labor is separated by type of work: economic and household. After controlling for individual and household characteristics that determine child labor, we find that armed conflict intensity is associated with a higher likelihood of entry into economic work sufficient to qualify as child labor, but is not associated with entry into household child labor. However, conflict intensity is associated with marginal increases in hours worked for both types of activity. We also explore gender differences. These results provide further evidence of the long-term costs of war on households.